General geology and geochemistry of soil in Kampung Batu Melintang, Jeli, Kelantan. - Priyadarshini A/P Karunanadi (2016)
Batu Melintang situated around 15km away from UMK. This study area is bordered by latitude of 5° 41' 30" N to 5°44'35"N and longitude of 101°43'15"E to 101°46'20"E. The study area is 5 km x 5 km which can be access by road. The aim of this paper are to update the geological map of the study area in 1:25,000 scale, to study the heavy metals such as, Pb, Cd, Cu and Zn and cations concentration such as Sodium (Na+), Potassium (K+), Magnesium (Mg2+) and Calcium (Ca2+) in soil. The methods used are preliminary studies, followed by field work and laboratory work. For laboratory analysis, a few experiments were conducted such as pH, moisture content, organic matter, cation concentration, and heavy metals concentration. The lithologies found in this area are marble, schist and hornfels. The minerals that are identified in the lithology are mostly quartz in hornfels and schist. The major trending is from the direction NE-SW interpreted from negative lineament and joints analysis. The cation concentrations in the soil are at stable level where cations are responsible for nutrients uptake between soil and plant roots. The total cation concentrations in the study area are increasing in the following order: Mg2+<Ca2+<Na+<K+. Heavy metals analysis has showed the contamination in the soil in the study area. The concentration of heavy metals was in the following decreasing order: Zn > Cu > Pb > Cd. The remediation step should be taken in certain locations to control the contamination in the soil in order to reduce the hazard.